HUMAN RIGHTS IMPLEMENTATION ON INDONESIAN NATIONALITY LAW - Koesmoyo Ponco Aji (Polteknik Imigrasi, 2018)
Since introduced with Universal Declaration at 1948 by United Nations Organization, human rights has becoming a main instrument in international law and national laws. In Indonesia, regulations concerning human rights has been legalized by Act Number 39 Year 1999. Study is needed to explosure the extend of the rules of human rights that has determined in Indonesia Laws. This journal analyze Indonesia Nationality Law based on universal instrument of human rights by descriptive analysis research. Its found that Act Number 12 Year 2006 concerning Nationality of the Republic of Indonesia has accommodate universal instrument of human rights.